Successful International and Hungarian Family Businesses - Tobak, Júlia; Nábrádi, András; Nagy, Adrián Szilárd (International Journal of Engineering and Management Sciences, 2018)
The purpose of family businesses are maintaining market competitiveness, develop sustainably and achieve their results in the dynamic market environment. The family run businesses are contributing significantly to the economic growth. They are interested in long-term preservation of values. The study presents the charachteristics of the world’s TOP family owned companies. In order to proving the economic value and importance of the Hungarian family businesses the study contains some findings of a representative national.